1982
DOI: 10.1002/bjs.1800690807
|View full text |Cite
|
Sign up to set email alerts
|

Does calcitonin cause hypocalcaemia after thyroidectomy?

Abstract: Plasma calcitonin, parathyroid hormone, total thyroid hormones and calcium were measured in 6 patients before, during and after thyroidectomy for hyperthyroidism. In 4 patients, plasma calcium fell postoperatively by 0.23--0.46 mmol/l, but there was no change in calcitonin or parathyroid hormone levels. In one patient, in whom there was a postoperative fall in plasma calcium of 0.55 mmol/l, thyroid hormones rose to a peak at 1 h and calcitonin to a peak at 12 h after resection. However, the rise in calcitonin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Such discrepancy can be explained by considering that: (i) thyroidectomy produces the complete depletion of thyroid hormones, while the pharmacologically induced hypothyroidism evokes a partial reduction of thyroid hormones; (ii) the possibility that hypocalcaemia, as a common consequence of thyroidectomy, could affect the normal function of several tissues (Sawers et al. ); (iii) in contrast to rats, rabbits can stay in an stable early proestrus by light/dark cycle regulation (Mousa‐Balabel and Mohamed ); and/or (iv) an inadequate regionalization or sampling of oviductal regions, including transitional zones, that could misled precise interpretations as previously proposed (Pedrero‐Badillo et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Such discrepancy can be explained by considering that: (i) thyroidectomy produces the complete depletion of thyroid hormones, while the pharmacologically induced hypothyroidism evokes a partial reduction of thyroid hormones; (ii) the possibility that hypocalcaemia, as a common consequence of thyroidectomy, could affect the normal function of several tissues (Sawers et al. ); (iii) in contrast to rats, rabbits can stay in an stable early proestrus by light/dark cycle regulation (Mousa‐Balabel and Mohamed ); and/or (iv) an inadequate regionalization or sampling of oviductal regions, including transitional zones, that could misled precise interpretations as previously proposed (Pedrero‐Badillo et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst hypoparathyroidism will reflect hypocalcaemia caused by non‐functioning parathyroid glands, it will not detect hypocalcaemia caused by thyrotoxic osteodystrophy where PTH will be present (low/normal/elevated). 10,25,2931 It is therefore important to combine PTH and serum calcium monitoring to accurately predict hypocalcaemia.…”
Section: Discussionmentioning
confidence: 99%
“…15,[23][24][25][26][27][28] Whilst hypoparathyroidism will reflect hypocalcaemia caused by nonfunctioning parathyroid glands, it will not detect hypocalcaemia caused by thyrotoxic osteodystrophy where PTH will be present (low/normal/elevated). 10,25,[29][30][31] It is therefore important to combine PTH and serum calcium monitoring to accurately predict hypocalcaemia. Several investigators have reported measuring serial serum calcium (total or ionised) in the early postoperative period (6 hours postoperation) to predict hypocalcaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing Parathyroid hormone stimulates the release of calcium from bone indirectly through the osteoblast. However, there is confl icting evidence as to whether the rise in calcitonin is coincident with, or after, the fall in calcium is seen (289,350). Osteoprotegerin (OPG) production in the osteoblast is inhibited by PTH.…”
Section: Calcitoninmentioning
confidence: 99%